Issues and prospects of mentorship development in Ukraine - Терюханова, І. М.; Дрозач, М. І.; Стульпінас, Н. К. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2017)
The article is devoted to development of mentorship system in Ukraine. The rode of mentorship for professional adaptation of personnel is described, key issues are highlighted and propositions are given to improve the organization of mentorship in Ukraine.